The Reciprocal Effect of Psychosocial Aspects on Nurses' Working Conditions - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek (Frontiers in Psychology, 2017)
Objectives: Psychosocial work risks are most often considered in the context of occupational stress. The aim of this article is to evaluate the correlations between different aspects of nurses’ psychosocial working conditions. Materials and methods: The study was conducted using the questionnaire: Psychosocial aspects of work. A total of 789 nurses working in inpatient health care facilities in Bialystok were included in the study. Correlation analysis was performed by determining Spearman's correlation coefficient. Results: Correlations between the primary scales, such as job demands, control, social support, well-being, and expectations of changes, were evaluated. The weakest correlation was shown between the assessment of job demands and other work aspects. The strongest correlation was found between the ability to control and social support. Perception of the need for changes was influenced by the assessment of job demands, components of the control scale and, most of all, the scale of social support. A strong correlation was found between physical and psychological well-being and support from superiors and coworkers. Conclusions: 1. The state of well-being had no effects on nurses’ assessment of the demands they were faced with. Nurses' well-being depended only on social support provided by their superiors and colleagues, the sense of being able to have an affect on the performed work, minimal conflicts, and absence of overload. 2. Management should enable adequate working conditions in order to ensure nurses' physical and psychological well-being, as both these aspects were closely correlated. 3. Poor social support, lack of a sense of control over one’s work, conflicts, and work overload were factors that promoted nurses' expectations of changes.